Synthesis of biodegradable and flexible, polylactic acid based, thermoplastic polyurethane with high gas barrier properties - Ali, Fathilah; Kang, Dong Jin; Kim, Minsoo P; Cho, Chul-Hee; Kim, Bumjoon J (Wiley, 2014)
Polylactic acid (PLA) has the beneficial properties of good mechanical strength, biodegradability and biocompatibility, and these properties make it suitable for use as an environmentally friendly packagingmaterial. However, its use has been limited by its brittleness and poor stability. In this work, we successfully developed an efficient synthesis scheme to improve the mechanical properties, flexibility and gas barrier properties of PLA-based polymers. Four different PLA-based thermoplastic polyurethane (PLAPU) polymerswere synthesized through the reaction of PLA diolwith hexamethylene diisocyanate, followed by chain extension with polycaprolactone (PCL) diol. The relative compositions of the hard PLA and the soft PCL diols in the PLAPU polymers were controlled systematically to optimize the physical properties of the polymers. For example, increasing the content of PCL resulted in higher molecular weight PLAPU polymers that had increased tensile strengths and elongations at break, but their moduli were decreased. At the optimized PLA:PCL ratio of 1:3, the PLAPU polymer had an excellent elongation at break of1053%with a relatively high Young’s modulus of 51.8 MPa. In addition, the gas barrier properties of the PLAPUswere significantly enhanced depending on the molecular weight and PCL content of the polymers. To demonstrate the feasibility of using PLAPU polymers for biodegradable packaging materials, hydrolytic degradation tests were performed in phosphate buffer solution, and the PLAPU polymers were degraded gradually at rates that depended on the content of PCL in the polymers. This optimized PLAPU polymer exhibited excellent flexibility and gas barrier property, as well as high elongation, demonstrating its potential utility as packagingmaterials.